Gastrointestinal Parasites and Bacteria in Free-Living South American Sea Lions (Otaria flavescens) in Chilean Comau Fjord and New Host Record of a Diphyllobothrium scoticum-Like Cestode - Hermosilla, Carlos; Hirzmann, Jörg; Silva, Liliana M. R.; Scheufen, Sandra; Prenger-Berninghoff, Ellen; Ewers, Christa; Häussermann, Vreni; Försterra, Günter; Poppert, Sven; Taubert, Anja (Frontiers in Marine Science, 2018)
Present study aimed to characterize gastrointestinal parasites and culturable bacteria from free-living South American sea lions (Otaria flavescens) inhabiting waters of Comau Fjord, Patagonia, Chile. Therefore, a total of 28 individual faecal samples were collected from sea lions within their natural marine habitat during several diving expeditions. Using classical parasitological techniques, study revealed infections with five different gastrointestinal parasite genera. In addition, bacterial cultures showed presence of at least 28 different bacterial genera. Referring to parasites, protozoan and metazoan species were found with some of them bearing anthropozoonotic potential and/or pathogenic impact for these marine mammals. As such, four of identified parasite genera harbored zoonotic potential (i. e. Entamoeba, Balantidium, Diphyllobothrium, Anisakis) and one genus (Parafilaroides) represented a specific lungworm of marine pinnipeds. Proglottids from faecal samples showed high morphological homology to ‘Diphyllobothrium’ scoticum (Rennie and Reid, 1912) Meggitt, 1924, which was found in Antarctic sea leopards (Hydrurga leptonyx; Phocidae), but contained eggs of smaller size. Molecular characterization revealed 97–100% identity to a new `Diphyllobothrium´ species which was recently isolated from a Californian sea lion (Zalophus californianus; Otariidae) in San Francisco. As such, O. flavescens represents a new host record for this parasite species. Furthermore, potential zoonotic bacteria (i. e. Clostridium, Escherichia, Vibrio, Yersinia, Salmonella) were identified amongst others in O. flavescens indicating a reservoir role for these pinnipeds in marine ecosystem. Current data should be considered as a baseline study for future monitoring surveys on anthropozoonotic pathogens circulating in wild free-living sea lions and their possible impact on public health issues and marine wildlife.